Impact on Radiation Dose and Volume V57 Gy of the Brain on Recurrence and Survival of Patients with Glioblastoma Multiformae - Stojkovski, Igor; Krstevska, Valentina; Smichkoska, Snezhana (Walter de Gruyter GmbH, 2017)
The aim of the study was to analyze impact of irradiated brain volume V57 Gy (volume receiving 57 Gy and more) on time to progression and survival of patients with glioblastoma.